Penerapan Pendidikan Agama Hindu Dan Budi Pekerti Dalam Membentuk Karakter Siswa - Widiasanti, Ni Made; Suardika, I Kadek (Jayapangus Press, 2021)
Education not only aims to educate, teach and create quality children and have good character in order to achieve the goals to be achieved, be able to adapt and socialize well and quickly in society and the surrounding environment. Lack of character education will cause a moral crisis that will have an impact on the emergence of bad or negative character. Children in the view of Hinduism and Budi Pekerti teachings are saviors for parents and ancestors, because children will continue their descendants. Therefore, the teachings of Hinduism are functioned as part of learning aimed at character education. This research uses a type of qualitative research using a descriptive analysis approach. The results of this study indicate that Hindu Religious Education and Budi Pekerti is a source of students to gain knowledge, understanding and skills to shape the morals and character of students to be better. Therefore, Hindu Religious Education and Budi Pekerti have a very big role in shaping student character by doing direct practice or holding extracurricular activities related to religion. The application of Hindu Religious Education and Budi Pekerti can also be seen from the habits, actions and behavior of students. Hinduism and Budi Pekerti education teachers can provide education that leads to the development of morals and ethics for students in the teaching and learning process. The implementation of the application of Hinduism and Budi Pekerti values provided by teachers at school to shape student character can be seen from the habits of students at school, at home and in the community.